Sociology of religion a reader - Mirola, William A. (William Andrew); Emerson, Michael O. 1965-; Monahan, Susanne C. (Routledge, 2019)
"Sociology of Religion is a collection that seeks to explore the relationship between the structure and culture of religion and various elements of social life in the United States. This reader is a ... standalone course text and can also serve as supplement to the text written by the same author team, Religion Matters (Routledge, 2010). Based on both classic and contemporary research in the sociology of religion, this new, third edition highlights a variety of research methods and theoretical approaches to studying the sociological elements of religion. It explores the ways in which religious values, beliefs and practices shape the world outside of church, synagogue, or mosque walls while simultaneously being shaped by the non-religious forces operating in that world."--Provided by publisher.